2013
DOI: 10.1016/j.parint.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Whole-cell patch-clamp recording of nicotinic acetylcholine receptors in adult Brugia malayi muscle

Abstract: Lymphatic filariasis is a debilitating disease caused by clade III parasites like Brugia malayi and Wuchereria bancrofti. Current recommended treatment regimen for this disease relies on albendazole, ivermectin and diethylcarbamazine, none of which targets the nicotinic acetylcholine receptors in these parasitic nematodes. Our aim therefore has been to develop adult B. malayi for electrophysiological recordings to aid in characterizing the ion channels in this parasite as anthelmintic target sites. In that reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 18 publications
(18 reference statements)
3
30
0
Order By: Relevance
“…The results presented here are similar to those reported for adult female B. malayi, where 30 lM levamisole inhibited motility by 85 % in 10 min, but the worms recovered within an hour (Robertson et al 2013). Possible reasons for the transient paralysis seen in 1 mM levamisole might be that this concentration of drug causes the nAChRs at the neuromuscular junction to be downregulated or otherwise desensitized (Taly et al 2009).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The results presented here are similar to those reported for adult female B. malayi, where 30 lM levamisole inhibited motility by 85 % in 10 min, but the worms recovered within an hour (Robertson et al 2013). Possible reasons for the transient paralysis seen in 1 mM levamisole might be that this concentration of drug causes the nAChRs at the neuromuscular junction to be downregulated or otherwise desensitized (Taly et al 2009).…”
supporting
confidence: 87%
“…It and other nicotinic agonists are widely used as anthelmintic drugs against gastrointestinal parasites of livestock, but have not been widely used against filarial parasites which inhabit tissues other than the GI tract. Recently, it has been shown that adult Brugia malayi, the causative agent of about 10 % of cases of lymphatic filariasis, possesses levamisole-sensitive nAChRs (Robertson et al 2011(Robertson et al , 2013. We therefore undertook to study the effect of the drug on the locomotion of microfilariae (Mf).…”
mentioning
confidence: 99%
“…In Ascaris suum, there are three separable muscle subtypes [N-, L-, and B- (27)] and four types in Oesophagostomum dentatum (11). Xenopus expression experiments suggest in Haemonchus contortus and Oesophagostomum dentatum that: the L-type (L-AChR-1) is composed of UNC-63, UNC-38, UNC-29, and ACR-8 subunits; the P-type (L-AChR-2) is composed of UNC-63, UNC-38, and UNC-29 subunits (10,25); and the N-type in Ascaris suum is composed of ACR-16 subunits (14,35,50). A fourth type of muscle nAChR selectively activated by morantel and composed of ACR-26 and ACR-27 subunits has been described in Haemonchus contortus (51).…”
Section: Discussionmentioning
confidence: 99%
“…Their neuromuscular systems are unlike those of vertebrates because nematode muscles send processes to the motor neurons to form synapses, rather than the other way around. Membrane ion-channels, which regulate nematode neuromuscular systems, are target sites of major classes of anthelmintic drugs, including the cholinergic anthelmintics levamisole, pyrantel, and derquantel (10)(11)(12)(13)(14)(15)(16)(17). Here, we have combined a number of techniques for the study of muscle pentameric acetylcholine receptor channels (nAChRs) of the filarial nematode parasite, Brugia malayi.…”
mentioning
confidence: 99%
See 1 more Smart Citation